Experimental Research on foam Concrete with Partial Replacement of Fine Aggregates by Blast Furnace Slag, Fly Ash, and Glass Powder (International Journal of Innovative Research in Engineering & Management, 2023)
Although foam concrete was initially  intended to be avoid filler and insulating material, interest  in its structural qualities has grown again due to its reduced  weight, material savings, and potential for extensive use of  waste materials like fly ash. This paper's main objective is  to review the present state of knowledge on foam concrete,  where sand is partially replaced by glass powder, fly ash,  and blast furnace slag in various weights and proportions.  The review highlights the necessity for creating new  pathways by doing in-depth research on materials, mixture  design, and methods to maximise the potential of this  material for structural applications.
Keywords: Foam concrete; Light weight; blast furnace slag; fly ash and glasspowder and compressive strength